AI-driven mediation and legal assistance: A multilingual chatbot model for effective dispute resolution - Yadav, Abhishek; Yadav, Mohit; Samriti, Samriti; Singh, Pranchal; Mohamed, Ali Wagdy; Khalaf, Osamah Ibrahim; Khang, Alex (Edelweiss Applied Science and Technology, 2026)
In the previous few decades, as people have been dissatisfied with the excessive inefficiencies associated with the traditional process of civil litigation, new solutions such as mediation through AI chatbots have gained popularity in the modern age. The increase in civil filings (58%) over the last three years compared with pre-COVID levels, as well as long periods for cases (average of 25 months), are cases that require immediate action to create solutions for faster and more affordable avenues to resolving disputes. AI chatbots offer the opportunity for a more efficient, rational way of resolving disputes because they provide 24/7 service, multilingual capabilities, and personalized assistance. The current proposed work analyzes the chatbot technology, which utilizes natural language processing (NLP) and machine learning (ML) to read through cases, provide guidance on the best mediation process, and, for some, match consumers with mediators. Additionally, this technology will incorporate legal databases (such as LexisNexis and Westlaw), as well as integrate speech-to-text capabilities, use blockchain for secure data storage, and more to create processes that are not only lower in volume but also provide faster resolutions and higher user satisfaction. Actual applications, such as in New York and California, have shown encouraging results with as much as a 50% drop in trial rates. Developments in technology in the near future will also include virtual reality (VR) mediation preparation, AI-generated documents, and predictive analytics, all aimed at continuing to disrupt the system of access to justice.